Love or Loss: Effective message framing to promote environmental conservation. Issue 3 (3rd July 2019) - Jacobson, Susan K.; Morales, Nia A.; Chen, Beida; Soodeen, Rebecca; Moulton, Michael P.; Jain, Eakta
ABSTRACT: Understanding the influence of message framing is critical to promote public support for environmental conservation. We tested six brief, online videos about biodiversity conservation with positive (love and benefits) versus negative (loss and warning) messages with 524 participants. The respondents were willing to donate more money and time to organizations associated with positively framed videos. Contrary to the other studies, neither the gender nor level of audience involvement in environmental issues influenced response to positive or negative messaging. Findings highlight the use of positive messaging in digital media campaigns and encourage environmental practitioners to refine and test their messages with specific audiences.